2020
DOI: 10.1093/nar/gkaa319
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a novel immune-evasion strategy from an ancestral protein fold in bacteriophage Mu

Abstract: The broad host range bacteriophage Mu employs a novel ‘methylcarbamoyl’ modification to protect its DNA from diverse restriction systems of its hosts. The DNA modification is catalyzed by a phage-encoded protein Mom, whose mechanism of action is a mystery. Here, we characterized the co-factor and metal-binding properties of Mom and provide a molecular mechanism to explain ‘methylcarbamoyl’ation of DNA by Mom. Computational analyses revealed a conserved GNAT (GCN5-related N-acetyltransferase) fold in Mom. We de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Based on many studies of the chemical and kinetic mechanisms of GNAT enzymes, it is clear this superfamily has evolved to utilize a diversity of chemistries and active site residues for more complex and targeted modifications of acceptor substrates. Identification of additional non-acyl transfer reactions for GNATs, including decarboxylation, methylcarbamoyl transfer, and condensation ( Gu et al, 2007 ; Izoré et al, 2019 ; Karambelkar et al, 2020 ; Skiba et al, 2020 ) highlight the shear multitude of chemistries that enzymes from this superfamily can accomplish. Thus, GNATs appear to have a highly tunable scaffold that has evolved to modify a diverse range of substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Based on many studies of the chemical and kinetic mechanisms of GNAT enzymes, it is clear this superfamily has evolved to utilize a diversity of chemistries and active site residues for more complex and targeted modifications of acceptor substrates. Identification of additional non-acyl transfer reactions for GNATs, including decarboxylation, methylcarbamoyl transfer, and condensation ( Gu et al, 2007 ; Izoré et al, 2019 ; Karambelkar et al, 2020 ; Skiba et al, 2020 ) highlight the shear multitude of chemistries that enzymes from this superfamily can accomplish. Thus, GNATs appear to have a highly tunable scaffold that has evolved to modify a diverse range of substrates.…”
Section: Discussionmentioning
confidence: 99%
“…S6), the structure shows that Mom forms tight dimers with an interface area of ~850 Å 2 , and a predicted free energy of binding of 4.7 kcal/mol according to the PISA server (32). As anticipated (16,17,31), Mu Mom protomers have the GNAT fold, but with an atypical insertion spanning residues ~175-209 that visually resembles a helixturn-helix (HTH) motif (Fig. 3A-3D) (33)(34)(35).…”
Section: Crystal Structure and Mutants Reveal Putative Active Site An...mentioning
confidence: 75%
“…1A), reporting an unusual carbamoylmethyl (glycinamide) group at the N6-position of adenine (abbreviated as 6-NcmdA) (13). These foundational studies on Mu also identified a gene, mom (modification of Mu), necessary for the installation of 6-NcmdA during late stages of Mu infection (7)(8)(9)(10)(11)(14)(15)(16)(17). More recently, it was established that mom is the only phage Mu gene required for hypermodification of dA (fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the last gene in Thornton (gp 43) and SerPounce is functionally annotated as a GNAT family acetyltransferase. These proteins exhibit homology to Escherichia phage Mu methylcarbamoylase mom, which is predicted to modify ~15% of adenine residues in viral DNA to make it resistant to type 1/II restriction enzymes [ 64 ]. A region containing 21 bp of identity was identified on both sides of this gene in the Thornton genome ( Figure 8 c,d), compared to a single copy of this region in Juan.…”
Section: Resultsmentioning
confidence: 99%